PENANGGULANGAN KEKERASAN DALAM RUMAH TANGGA DI KOTA MEDAN DITINJAU DALAM HUKUM PIDANA ISLAM - Hazar, Siti; Ramadani, Ramadani (Legal Standing : Jurnal Ilmu Hukum, 2024)
The review of Islamic criminal law and the prevention of domestic violence in Medan City are the two topics examined in this research and study. Although this research strategy is a case approach, the author uses empirical juridical research in this study. In addition, this research is studied descriptively qualitatively to find out the enforcement of Islamic criminal law against cases of domestic violence (KDRT). However, this research approach is a case approach. This research uses primary data, namely information obtained directly from the person concerned, by conducting interviews and field research at the PPA Unit of the Medan Police Criminal Investigation Unit. Literature from books, journals relevant to the research topic, and fiqh texts were used as secondary sources of information for this research. According to the findings of this research, the lack of a formal legal umbrella in Medan City makes it impossible to conduct criminal mediation in cases of domestic violence. As part of their responsibilities, local governments and social organizations are charged with the responsibility to provide victim recovery facilities. To provide assistance to victims of domestic violence, the recovery providers work together. During an interview with the PPA Unit of Medan Police Station, the author found that the police will cooperate with the office to assist victims in evaluating the mental health of victims of domestic violence in Medan City.